Issues and research agenda for Malaysian SMEs revisited - Hashim, Mohd Khairuddin; Ahmad, Sa'ari (Universiti Utara Malaysia Press, 2005)
Small and medium-sized enterprises (SMEs) represent an important part of the Malaysian business system. Notwithstanding their economic importance, research on SMEs is still limited and neglected. The literature review indicates SML in Malaysia have attracted minimal theoretical as well as empirical research attention from researchers as a field of study.Based on the review of the small business literature, this paper initiates an attempt to provide a research agenda for studying SMEs in Malaysia stressing the shortcomings of past studies as well as well as highlighting the major issues and research areas that have yet to be explored and benefited by future researchers.